Multiple Anesthesia/Surgery Cannot Impair Reference Memory in Adult Mice - Xiaoxin Zhou; Jian Lu; Tong Wu; Xuliang Jiang; Weitian Tian; Wanbing Dai; Siyi Qi; Xuemei Chen; Jiaqiang Zhang; Diansan Su (Hindawi Limited, 2020)
Postoperative cognitive dysfunction increases mortality and morbidity in perioperative patients. Numerous studies have demonstrated that multiple surgery/anesthesia during the neurodevelopmental period affects cognitive function, whereas a single anesthesia/surgery rarely causes cognitive dysfunction in adults. However, whether adults who undergo multiple anesthesia/surgery over a short period will experience cognitive dysfunction remains unclear. In this study, central nervous system inflammation and changes in cholinergic markers were investigated in adult mice subjected to multiple laparotomy procedures over a short period of time. The results showed that despite the increased expression of IL-6 and TNF-α in the hippocampus after multiple operations and the activation of microglia, multiple anesthesia/surgery did not cause a decline in cognitive function in adult mice. There were no changes in the cholinergic markers after multiple anesthesia/surgery.